2016
DOI: 10.22159/ajpcr.2017.v10i1.14163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Ethanolic Extract of Curanga Fel-Terrae (Pugun Tano) Leaves on Acetylcholine Muscarinic-3 Receptors Induced on Isolated Guinea Pig Tracheal

Abstract: Objective: The study was aimed to investigate the inhibitory effect of ethanolic extract of Curanga fel-terrae leaves (EECFL) against acetylcholine (ACh)-induced contraction of the ACh-muscarinic-3 receptor. Materials and Methods:The study of the inhibitory effect of the ethanolic extract on the contraction by ACh concentration series (10 −8 -10 −3 M) was conducted in vitro using isolated guinea pig tracheal organ in the Krebs solution.Results: Early incubation of tracheal organ with EECFL (0.5, 1, 2 and 4 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…+ due to Dox administration. Preliminary phytochemical screening of ethanolic extract of Picria fel-terrae leaves indicated that the presences of flavonoids, saponins, triterpenes, and steroids [25]. Some flavonoids showed anticancer and immunomodulatory activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…+ due to Dox administration. Preliminary phytochemical screening of ethanolic extract of Picria fel-terrae leaves indicated that the presences of flavonoids, saponins, triterpenes, and steroids [25]. Some flavonoids showed anticancer and immunomodulatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Reportedly showed that this plant contained glycoside, flavonoid, saponin, terpenoid, curangin, and bitter compound [2], [3], [4], [5], [6], [7], [8]. The pharmacological activity of this plant also has been studied such as anthelmintic, antidiabetic, anti-breast cancer, diuretic effect, cardioprotective effect, and antimuscarinic receptor [2], [9], [14].…”
Section: Introductionmentioning
confidence: 99%
“…At the maximum dose, there was no death in the acute toxicity experimental animal. The above-mentioned dose did not change in general behavior or any clinical signs of toxicity [25].…”
Section: Acute Toxicitymentioning
confidence: 75%
“…In Indonesia, these plants are spread in Sumatra, Java, Kalimantan, and Maluku. C. fel-terrae often used by the Karo tribe of Tiga Lingga Village, Kabupaten Dairi, Provinsi Sumatera Utara to treat diarrhea, asthma, cough, scabies, inflammation, bruising, and abdominal pain [5]. C. fel-terrae has many benefits for treating various diseases not only empirically proven but also scientifically.…”
Section: Introductionmentioning
confidence: 99%